Ergonomics in the anaesthetic workplace: Guideline from the Association of Anaesthetists. (12th July 2021) - Bailey, C. R.; Radhakrishna, S.; Asanati, K.; Dill, N.; Hodgson, K.; McKeown, C.; Pawa, A.; Plaat, F.; Wilkes, A.
Summary: Ergonomics in relation to anaesthesia is the scientific study of the interaction between anaesthetists and their workspace environment in order to promote safety, performance and well‐being. The foundation for avoiding pain or discomfort at work is to adopt and maintain a good posture, whether sitting or standing. Anaesthetists should aim to keep their posture as natural and neutral as possible. The successful practice of anaesthesia relies on optimisation of ergonomics and lack of attention to detail in this area is associated with impaired performance. The anaesthetic team should wear comfortable clothing, including appropriately‐sized personal protective equipment where necessary. Temperature, humidity and light should be adequate at all times. The team should comply with infection prevention and control guidelines and monitoring as recommended by the Association of Anaesthetists. Any equipment or machinery that is mobile should be positioned where it is easy to view or reach without having to change the body or head position significantly when interacting with it. Patients who are supine should, whenever possible, be raised upwards to limit the need to lean towards them. Any item required during a procedure should be positioned on trays or trolleys that are close to the dominant hand. Pregnancy affects the requirements for standing, manually handling, applying force when operating equipment or moving machines and the period over which the individual might have to work without a break. Employers have a duty to make reasonable adjustments to accommodate disability in the workplace. Any member of staff with a physical impairment needs to be accommodated and this includes making provision for a wheelchair user who needs to enter the operating theatre and perform their work. 요약: 마취와 관련된 인체 공학은 안전, 수행과 웰빙을 증진하기 위한, 마취과 의사의 작업 공간 환경 간 상호작용에 대한 과학적 연구이다. 근무 중 통증이나 불편함을 없애는 기본은 앉든지 서든지 좋은 자세를 취하고 유지하는 것이다. 마취과 의사는 가능한 자연스럽고 중립적인 자세를 유지하는 것을 목표로 해야 한다. 성공적 마취 수행은 인체 공학을 최적화하는 것에 달려 있으며, 이 영역의 세부사항들에 대한 주의 부족은 수행능력 저하와 관련된다. 마취팀은 필요한 경우 적절한 크기의 개인 보호 장비를 포함하여 편안한 의복을 착용해야 한다. 온도, 습도와 빛은 항상 적절해야 한다. 팀은 마취과 의사 협회에서 권고된 대로 감염 예방 및 통제 지침과 모니터링을 준수해야 한다. 움직일 수 있는 모든 장비나 기계는 사용 시 몸이나 머리 위치를 크게 바꾸지 않고도 쉽게 보거나 닿을 수 있는 곳에 위치해야 한다. 반듯하게 누운 환자들은 가능한 모든 경우 위로 올려져 마취과 의사가 그쪽으로 기울일 필요가 없도록 해야 한다. 시술 중 필요한 모든 물품은 주로 사용하는 손과 가까운 트레이나 카트에 배치해야 한다. 임신은 서는 것, 수동 조작, 장비를 작동시키거나 기계를 이동할 때 힘을 가하는 것, 개인이 휴식 없이 일해야 할 수 있는 기간에 영향을 미친다. 고용주는 직장에서 불편함에 대한 편의를 도모하기 위해 합리적 조정을 할 의무가 있다. 신체 장애가 있는 모든 직원은 편의가 도모되어야 하며, 여기에는 수술실에 들어가 업무를 수행해야 하는 휠체어 사용자를 위한 준비가 포함된다.